Day-and-night glycaemic control with closed-loop insulin delivery versus conventional insulin pump therapy in free-living adults with well controlled type 1 diabetes: an open-label, randomised, crossover study. Issue 4 (April 2017) - Bally, Lia; Thabit, Hood; Kojzar, Harald; Mader, Julia K; Qerimi-Hyseni, Jehona; Hartnell, Sara; Tauschmann, Martin; Allen, Janet M; Wilinska, Malgorzata E; Pieber, Thomas R; Evans, Mark L; Hovorka, Roman
Summary: Background: Tight control of blood glucose concentration in people with type 1 diabetes predisposes to hypoglycaemia. We aimed to investigate whether day-and-night hybrid closed-loop insulin delivery can improve glucose control while alleviating the risk of hypoglycaemia in adults with HbA1c below 7·5% (58 mmol/mol). Methods: In this open-label, randomised, crossover study, we recruited adults (aged ≥18 years) with type 1 diabetes and HbA1c below 7·5% from Addenbrooke's Hospital (Cambridge, UK) and Medical University of Graz (Graz, Austria). After a 2–4 week run-in period, participants were randomly assigned (1:1), using web-based randomly permuted blocks of four, to receive insulin via the day-and-night hybrid closed-loop system or usual pump therapy for 4 weeks, followed by a 2–4 week washout period and then the other intervention for 4 weeks. Treatment interventions were unsupervised and done under free-living conditions. During the closed-loop period, a model-predictive control algorithm directed insulin delivery, and prandial insulin delivery was calculated with a standard bolus wizard. The primary outcome was the proportion of time when sensor glucose concentration was in target range (3·9–10·0 mmol/L) over the 4 week study period. Analyses were by intention to treat. This study is registered withClinicalTrials.gov, numberNCT02727231, and is completed. Findings: Between March 21 and June 24, 2016, we recruited 31 participants, of whom 29 were randomised. One participant withdrew during the first closed-loop period because of dissatisfaction with study devices and glucose control. The proportion of time when sensor glucose concentration was in target range was 10·5 percentage points higher (95% CI 7·6–13·4; p<0·0001) during closed-loop delivery compared with usual pump therapy (65·6% [SD 8·1] when participants used usual pump therapy vs 76·2% [6·4] when they used closed-loop). Compared with usual pump therapy, closed-loop delivery also reduced the proportion of time spent in hypoglycaemia: the proportion of time with glucose concentration below 3·5 mmol/L was reduced by 65% (53–74, p<0·0001) and below 2·8 mmol/L by 76% (59–86, p<0·0001). No episodes of serious hypoglycaemia or other serious adverse events occurred. Interpretation: Use of day-and-night hybrid closed-loop insulin delivery under unsupervised, free-living conditions for 4 weeks in adults with type 1 diabetes and HbA1c below 7·5% is safe and well tolerated, improves glucose control, and reduces hypoglycaemia burden. Larger and longer studies are warranted. Funding: Swiss National Science Foundation (P1BEP3_165297 ), JDRF, UK National Institute for Health Research Cambridge Biomedical Research Centre, andWellcome Strategic Award (100574/Z/12/Z ).